PORTRAIT OF POST PANDEMI HISTORY LEARNING AT SMAN 1 BANYUPUTIH IN THE 2021/2022 ACADEMIC YEAR: POTRET PEMBELAJARAN SEJARAH PASCA PANDEMI DI SMAN 1 BANYUPUTIH PADA TAHUN PEMBELAJARAN 2021/2022 - Putri Fiska Fiyanti; I Kadek Yudiana; Mahfud (SOSIOEDUKASI, 2023)
This research was carried out with the aim of knowing learning during the pandemic and post-pandemic, especially to find out what strategies were applied in learning methods, using learning media and using learning resources. This research method uses qualitative methods and the type of research is a case study. The data collection methods used were observation, interviews and document studies. The results of this study are that history teachers at SMA Negeri 1 Banyuputih have implemented innovative learning as a strategy for dealing with teaching and learning activities during a pandemic and post-pandemic. By using various models and learning methods. The learning methods used are the Discovery Learning and Problem Blased Learning methods. The learning media used are media images, photos, PowerPoint and short video films. The learning resources used include sources from other books, the internet and discussions that are appropriate to the learning material.